Pendampingan Badan Usaha Milik Desa (BUMDES) Dalam Pemanfaatan Aset Melalui Optimalisasi Pemanfaatan Gelanggang Olahraga (GOR) - Reladi, Aliyah Putri; Mokoginta, Cindy Gabriella; Ilhamsyah, Shabrina Nur Amalina; Leza, Muhamad Rendy Apri; Alfiya, Nazla; As-sidiq, Bintang Nizar; Kadiyono, Anissa L (TAAWUN, 2024)
The establishment of Village-Owned Enterprises (BUMDes) is the government's effort to improve the original opinions of the village and improve the standard of living of villagers. However, without good management and the support of the government and the community, the hope to make BUMDes as a driver of the village economy may not be realized. The assistance in the management of BUMDes carried out is a form of concern in an effort to improve the economy of the village community. The method used is a capacity assessment of Bumdes using a qualitative method with interviews. The results of the assessment show that the Sports Arena (GOR) is an asset of BUMDes that can be intervened to empower GOR. GOR empowerment will increase village income and contribute towards ensuring the sustainability of BUMDes as a locomotive of the village economy.